2021
DOI: 10.1186/s12883-020-02019-1
|View full text |Cite
|
Sign up to set email alerts
|

Enriched Music-supported Therapy for chronic stroke patients: a study protocol of a randomised controlled trial

Abstract: Background Residual motor deficits of the upper limb in patients with chronic stroke are common and have a negative impact on autonomy, participation and quality of life. Music-Supported Therapy (MST) is an effective intervention to enhance motor and cognitive function, emotional well-being and quality of life in chronic stroke patients. We have adapted the original MST training protocol to a home-based intervention, which incorporates increased training intensity and variability, group session… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 95 publications
(103 reference statements)
0
10
0
Order By: Relevance
“…However, functional gains and transfer to everyday tasks are observed after at least 4 weeks of intervention and are even more noticeable after a second training period, thus suggesting progressive improvements ( Grau-Sánchez et al, 2018 , 2020 ). Importantly, recent intervention protocols have indicated that treatment intensity and duration may need to be increased to promote effective motor recovery for patients in the chronic stage of stroke ( Grau-Sánchez et al, 2021 ).…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…However, functional gains and transfer to everyday tasks are observed after at least 4 weeks of intervention and are even more noticeable after a second training period, thus suggesting progressive improvements ( Grau-Sánchez et al, 2018 , 2020 ). Importantly, recent intervention protocols have indicated that treatment intensity and duration may need to be increased to promote effective motor recovery for patients in the chronic stage of stroke ( Grau-Sánchez et al, 2021 ).…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Apart from adjusting the exercises to the level of participants’ ability, elements of the intervention can be chosen by patients to increase motivation and adherence to the intervention. It is common to allow the selection of different types of music according to the participant's preferences or the ideal time to do the intervention session in home‐based interventions 53,54 . These individual adjustments should be registered during data collection to consider them in the analysis or results interpretation.…”
Section: Treatmentmentioning
confidence: 99%
“…It is common to allow the selection of different types of music according to the participant's preferences or the ideal time to do the intervention session in home‐based interventions. 53 , 54 These individual adjustments should be registered during data collection to consider them in the analysis or results interpretation. Articles reporting the effectiveness of music‐based interventions should describe which elements of the training program were tailored and which were strategies to ensure treatment fidelity.…”
Section: Treatmentmentioning
confidence: 99%
“…The protocol of this study was approved by the Clinical Research Ethics Committee of the Bellvitge University Hospital (PR095/17; Barcelona, Spain) and the Hospitals del Mar i l'Esperança (Parc de Salut Mar, 2020/9523; Barcelona, Spain) and follows the Declaration of Helsinki to experiment with human beings (45). Participants signed an informed consent prior to participation explaining the feasibility objectives of the study and the absence of potential risks for completing the eMST intervention.…”
Section: Participantsmentioning
confidence: 99%
“…Secondary outcomes include other motor and cognitive functions, emotional well-being, and QoL measures as well as selfregulation and self-efficacy outcomes. Please see methods on the study protocol by Grau-Sánchez et al, 2021 (45) for more details.…”
Section: Main Study Outcomesmentioning
confidence: 99%